Economics of unlimited supply of labor and asymmetric power - Korkut Ertürk (The University of Utah, Department of Economics, 2015)
Since around 2000 the education premium and the level of employment in high-skill occupations has stagnated, if not actually begun to shrink. This brings into question the generally held view that in advanced countries, while potentially harmful for those who work with their hands, globalization and technological change benefit those who work with their minds. The paper argues that these unexpected labor market trends are the result not so much of autonomous changes in technology as much as they are that of the large power asymmetry between capital and labor that developed in the last few decades. The global oversupply of labor appears to have revived a pattern of skill replacing technological change that is reminiscent of 19th century capitalism. The relative abundance of cheap labor creates an incentive to chip away whatever component can be routinized from complex tasks that are performed by expensive skilled workers so that they can be offshored and automated. The paper develops a game theoretical definition of asymmetric power and shows why in labor markets characterized by a structural imbalance between supply and demand, market exchange ceases to be a positive-sum game, and how that can favor skill replacing technological change over one that augments skills. While autonomous innovations determine what non-routine task can at all be transformed into routine ones, the attractiveness of doing so is not independent of major shifts in labor market conditions.
Keywords: F60; J60; O33; D74; C72; B14; B25; 330; power in exchange; asymmetric power; institutional economics; skill-biased technological change; deskilling; globalization